Pendekatan Jaringan Saraf Tiruan untuk Memperkirakan Kinerja Mesin Pencacah Pelepah Sawit Terintegrasi [Artificial Neural Network Approach for Estimating Performance of Integrated Chopper Machine for Oil Palm Frond] - Agustami Sitorus; Ramayanty Bulan (Buletin Palma, 2019)
The working conditions of an appropriate oil palm chopper are important to be explored in order to improve the machine's performance while working. At present, the selection of working conditions depends on empirical rules and experimental trials. It is conducted because of the complex interaction between the unit of the integrated counter machine (cutting machine unit, compression machine unit, and chopper machine unit) to estimate its performance. Therefore, this study aims to estimate the performance of an integrated palm frond chopper machine through the Artificial Neural Network (ANN) approach. The design of the ANN model was carried out at the Research Center for Appropriate Technology in 2017-2019. Data input is as many as nine operating parameters collected from experimental tests in laboratory conditions using the AE01 type integrated palm fronds chopper machine. The ANN model architecture (input-layer-output) tested is [9-5-1], [9-10-1], and [9-15-1] with the Levenberg – Marquardt algorithm. The results of this study were obtained that the best prediction model is formed by a layered architecture of 10 layers, which results in a smaller prediction error value compared to the others. The model determination coefficient with that layer is 0.99862. Prediction of chopper performance using test data gives a coefficient of determination close to one. The mean squared error (MSE) of the model in each training phase, validation, and testing were 2,69´10-15, 1,56´10-4, 3,38´10-5.ABSTRAKKondisi kerja mesin pencacah pelepah sawit yang tepat penting ditelusuri guna meningkatkan performansi mesin saat bekerja. Saat ini, pemilihan kondisi kerja mesin tergantung pada aturan empiris dan uji coba eksperimental. Hal ini dilakukan karena interaksi yang kompleks antara unit bagian mesin pencacah terintegrasi (unit penggunting, pengempa dan pencacah) untuk memperkirakan kinerjanya. Penelitian ini bertujuan untuk memperkirakan kinerja mesin pencacah pelepah sawit terintegrasi melalui pendekatan Jaringan Saraf Tiruan (JST). Desain model JST dilakukan di Pusat Penelitian Teknologi Tepat Guna pada tahun 2017-2019. Parameter input data adalah sebanyak sembilan parameter operasi yang dikumpulkan dari uji coba eksperimental pada kondisi laboratorium menggunakan mesin pencacah pelepah sawit terintegrasi tipe-AE01. Arsitektur model JST (input-layer-output) yang diujicobakan adalah [9-5-1], [9-10-1], dan [9-15-1] dengan algoritma Levenberg–Marquardt. Hasil penelitian ini diperoleh bahwa model prediksi terbaik dibentuk dengan arsitektur layer sebanyak 10 buah yang menghasilkan nilai galat prediksi lebih kecil dibandingkan dengan yang lainnya. Koefisien determinasi model dengan layer tersebut adalah 0,99862. Prediksi kinerja mesin menggunakan data pengujian memberikan koefisien determinasi mendekati satu. Mean squared error (MSE) dari model pada masing-masing fase pelatihan, validasi dan pengujian adalah 2,69´10-15, 1,56´10-4, 3,38´10-5.